The study of agronomical traits determining productivity of Triticum aestivum/Triticum timopheevii introgression lines with resistance to fungal diseases - I. N. Leonova; E. B. Budashkina (Вавиловский журнал генетики и селекции)
Development of resistant cultivars is one of the effective ways for protection of common wheat T. aestivum L. from fungal pathogens. The gene pool of wild and cultivated wheat relatives is often used for widening the wheat genetic diversity of resistance genes. However, alien genetic material introgressed into the wheat genome can contain genetic factors negatively affecting agronomically important traits. T. aestivum/ T. timopheevii introgression lines derived from different common wheat cultivars have characteristically good resistance to leaf rust and powdery mildew. A comparative assessment of these lines and initial wheat varieties during four field seasons revealed a significant effect of environmental factors on the phenotypic differences between traits that have relevance to productivity. Averaged data obtained for individual introgression lines and for cross combinations revealed both positive and negative tendencies in variations of agronomical traits. The positive effects include a significant increase in the numbers of tillers and spikelets per spike of the lines derived from cv. Skala. Reduction in spike productivity was found in groups of the lines derived from cv. Tselinnaya 20 and cv. Novosibirskaya 67. However, no significant differences in 1000-grain weight were found between most lines and original wheat cultivars. Analysis of the data obtained showed no apparent correlation between the reduction of agronomic traits and the amount of alien genetic material introgressed into the common wheat genome. T. aestivum/T. timopheevii introgression lines can be used as a source of resistance genes without reducing the yield of wheat cultivars.